2007
DOI: 10.1002/ajh.21113
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in xenobiotic‐metabolizing genes and the risk of chronic lymphocytic leukemia and non‐Hodgkin's lymphoma in adult Russian patients

Abstract: Polymorphisms in genes coding xenobiotic-metabolizing enzymes are considered as risk factors modifying susceptibility to cancer. We developed a biochip for the analysis of 18 mutations in 10 genes of metabolizing system: CYP1A1, CYP2D6, GSTT1, GSTM1, MTHFR, MTRR, NQO1, CYP2C9, CYP2C19, and NAT2. Using allele-specific hybridization on the biochip 76 T-cell non-Hodgkin's lymphoma (NHL) patients, 83 B-cell chronic lymphocytic leukemia (B-CLL) patients, and 177 healthy donors were tested. Polymorphic CYP1A1 allele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
24
0
6

Year Published

2009
2009
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(32 citation statements)
references
References 46 publications
2
24
0
6
Order By: Relevance
“…This is in accordance with the studies of Kerridge et al (2002) and Al Dayel et al (2008). On the contrary, previous studies reported that there were no apparent association between the GSTT1 null genotype and NHL risk (Gra et al 2008, Sarmanova et al 2001Chiu et al 2005;Soucek et al 2002). As regards the eVect of gender on DLBCL risk, the risk increased in male patients harboring GSTT1 null genotype compared to male controls to be sixfold increased risk of DLBCL.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This is in accordance with the studies of Kerridge et al (2002) and Al Dayel et al (2008). On the contrary, previous studies reported that there were no apparent association between the GSTT1 null genotype and NHL risk (Gra et al 2008, Sarmanova et al 2001Chiu et al 2005;Soucek et al 2002). As regards the eVect of gender on DLBCL risk, the risk increased in male patients harboring GSTT1 null genotype compared to male controls to be sixfold increased risk of DLBCL.…”
Section: Discussionsupporting
confidence: 91%
“…Both GSTM1 and GSTT1 genes exhibit deletion polymorphisms, GSTM1 and GSTT1 null genotypes (Vogl et al 2004;Gra et al 2008). Individuals with deletions of GSTM or GSTT have reduced or no glutathione-S-transferase activity and, therefore, ineYcient detoxiWcation of various carcinogens, which could lead to genetic damage and increase the risk of somatic mutations leading to tumor formation (Coughlin and Hall 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The advanced age could be explained by the possible accumulation of toxic active metabolites in human tissues resulting from the decreased catalytic activity of detoxification enzymes due to the chronic exposure to genotoxic agents. However, data concerning CLL susceptibility regarding metabolizing genes are limited and sometimes contradictory [20]. To date, positive associations have been found only between polymorphic genes involved in the DNA damage-response and cell-cycle pathways and risk of CLL [20,21,22].…”
Section: Discussionmentioning
confidence: 99%
“…However, data concerning CLL susceptibility regarding metabolizing genes are limited and sometimes contradictory [20]. To date, positive associations have been found only between polymorphic genes involved in the DNA damage-response and cell-cycle pathways and risk of CLL [20,21,22]. The only proven relationship between CLL and detoxification genes concerns GSTs (glutathione-S-transferases), a superfamily of phase II enzymes, and it has been demonstrated that carrying more than one of the putative high-risk GST genotypes significantly increases the risk of developing CLL [20,23].…”
Section: Discussionmentioning
confidence: 99%
“…Изменение состояния ферментной редокс-системы глутатиона может определять чувствительность опухолевых клеток к лекарственным препаратам, применяемым в курсе химиотерапии [14,15].…”
unclassified